2020
DOI: 10.1177/1533033820956998
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of mRNAs and miRNAs Microarray Profiles to Screen miRNA Signatures Involved in Nasopharyngeal Carcinoma

Abstract: Objective: We aim to identify several microRNAs (miRNAs/miRs)-messenger RNAs (mRNAs) biomarkers correlated to nasopharyngeal carcinoma (NPC) based on an integrated analysis of miRNA and mRNAs microarray expression profiles. Methods: The available mRNA and miRNA microarray datasets were retrieved from Gene Expression Omnibus (GEO) database according to pre-determined screening criteria. Differentially expressed miRNA and mRNAs (DEmiRNAs and DEmRNAs) were extracted between NPC and noncancerous nasopharyngeal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…a noninvasive diagnostic tool and numerous studies have reported the diagnostic capacity of total RNA in the serum or plasma of patients for NPC. 20,21 However, it should be mentioned that the free-floating circulating miRNAs and sEV-derived miRNAs in the plasma or serum are independent forms, which are distinguished from each other. A previous study identified a 5-miRNA signature for the diagnosis of NPC in serum samples, but did not observe any significant differences for any of the 5 miRNAs in serum-derived exosome samples.…”
Section: Discussionmentioning
confidence: 99%
“…a noninvasive diagnostic tool and numerous studies have reported the diagnostic capacity of total RNA in the serum or plasma of patients for NPC. 20,21 However, it should be mentioned that the free-floating circulating miRNAs and sEV-derived miRNAs in the plasma or serum are independent forms, which are distinguished from each other. A previous study identified a 5-miRNA signature for the diagnosis of NPC in serum samples, but did not observe any significant differences for any of the 5 miRNAs in serum-derived exosome samples.…”
Section: Discussionmentioning
confidence: 99%
“…The tumorigenesis and progression of NPC are closely related to genetic factors, environmental effects, and Epstein–Barr virus (EBV) infection ( 6 ). Advanced NPC had worse clinical outcomes due to delayed diagnosis and distant metastasis are the critical factors for treatment failure ( 7 ). Consequently, it is necessary to identify novel biomarkers and investigate the molecular mechanisms for improving early diagnosis and prognosis of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al identified the histological specific biomarkers of miRNAs-mRNAs related to NPC based on the comprehensive analysis of miRNAs and mRNAs microarray. The results showed that miR-452-ITGA9 was obviously related to the survival rate of NPC invalids [ 8 ].…”
Section: Introductionmentioning
confidence: 99%